2021
DOI: 10.1088/1742-6596/1855/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environment Temperature on The Attenuation of Quasi-Spherical EFP Velocity

Abstract: A comparison of multiple quasi-spherical EFP warhead tests conducted during different seasons of the year revealed that EFP velocities in the cold season were low. In this paper, the experimental phenomenon is analyzed theoretically base on the principles of EFP and flight dynamics. Due to the difference of air density caused by the different temperature, the aerodynamic drag of EFP with the same aerodynamic shape and initial velocity is obviously different. Because of the hypervelocity of EFP, The impact velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Berner et al [ 12 ] carried out a theoretical analysis of the flight characteristics of EFPs in air. Li et al [ 13 ] made a theoretical analysis based on the EFP principle and flight dynamics principle and found that EFP aerodynamic resistance was significantly different when air density was different due to different temperatures. Liu et al [ 14 ] designed a new two-wing EFP, which improved the penetration capability of the EFP.…”
Section: Introductionmentioning
confidence: 99%
“…Berner et al [ 12 ] carried out a theoretical analysis of the flight characteristics of EFPs in air. Li et al [ 13 ] made a theoretical analysis based on the EFP principle and flight dynamics principle and found that EFP aerodynamic resistance was significantly different when air density was different due to different temperatures. Liu et al [ 14 ] designed a new two-wing EFP, which improved the penetration capability of the EFP.…”
Section: Introductionmentioning
confidence: 99%